PEMBINAAN KARAKTER SISWA MELALUI PROGRAM TADARUS AL-QUR’AN - Yeni Muyasyaroh; Hakimuddin Salim (PAI RAFAH, 2023)
This research aims to describe the character development of students through the Al-Qur'an tadarus program along with supporting and inhibiting factors. At the beginning of the observation at MTs Negeri 4 Sragen there was a Al-Qur'an tadarus program carried out in class, leading this activity was the teacher who taught starting from a predetermined letter. This Tadarus Al-Qur'an is carried out from Monday to Saturday together in each class, directed by the teacher before the start of the lesson. In carrying out reading the Koran, there are students who have not focused on reading, talk to their classmates, some are busy themselves, and so on. This research uses qualitative research with a descriptive phenomenological approach. The data sources obtained were the head of the curriculum, Qur'an hadith teachers, and moral aqidah teachers. Data analysis techniques use data reduction (investigating data), data display (data presentation), and data verification (drawing conclusions). validity of research data using source triangulation and technical triangulation. The process of developing student character through the Al-Qur'an tadarus program at MTs Negeri 4 Sragen has been going well, it can be seen from the habituation carried out by the school, including Al-Qur'an tadarus which can foster a personality that likes reading and discipline. Every morning at MTs Negeri 4 Sragen, they carry out Al-Qur'an tadarus activities before the start of lessons. Judging from some children today, reading the Al-Qur'an is not as good as makhroj and tajwid, but there are some children who are quite good at reading it. This is driven by the children themselves who stay at home playing on their cell phones more than reading the Koran with self-awareness and discipline. Therefore, schools organize Al-Qur'an reading activities to help students develop character by encouraging them to read the Al-Qur'an regularly and have the ability to read when they graduate.